2008
DOI: 10.1039/b718077b
|View full text |Cite
|
Sign up to set email alerts
|

“Click”-functionalization of conducting poly(3,4-ethylenedioxythiophene) (PEDOT)

Abstract: Efficient post-functionalization of conductive polymer films was achieved by Cu(+)-catalyzed "click"-cycloaddition of novel poly(azidomethyl-EDOT) and various functionalized terminal alkynes under mild heterogeneous conditions with high conversion efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 48 publications
8
84
0
Order By: Relevance
“…Compared to these measurements, the current intensity for bare gold electrodes tested in electrolyte solution free of monomer (100 mM TBAPF 6 in DCM) was very low. After addition of the azido-EDOT monomer to the electrolyte, a large current increase was observed at around 1 V, corresponding to the polymerization of the monomer, as reported by Bu et al (2008). In the second polymerization scan, a new irreversible redox wave was detected in the low-potential region, indicating the deposition of azido-PEDOT on the gold electrode.…”
Section: Dna Hybridizationmentioning
confidence: 52%
See 3 more Smart Citations
“…Compared to these measurements, the current intensity for bare gold electrodes tested in electrolyte solution free of monomer (100 mM TBAPF 6 in DCM) was very low. After addition of the azido-EDOT monomer to the electrolyte, a large current increase was observed at around 1 V, corresponding to the polymerization of the monomer, as reported by Bu et al (2008). In the second polymerization scan, a new irreversible redox wave was detected in the low-potential region, indicating the deposition of azido-PEDOT on the gold electrode.…”
Section: Dna Hybridizationmentioning
confidence: 52%
“…Azidomethyl-substituted 3,4-ethylenedioxythiophene (azido-EDOT) was synthesized following the protocol developed by Bu et al (2008). 99.8% anhydrous dichloromethane (DCM) and tetrabutylammonium hexafluorophosphate (TBAPF6) were supplied by Sigma-Aldrich Co. (USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,11] This is one of the most widely applied reactions in the area of ''click chemistry'', as defined by Sharpless and coworkers. [12] Other authors independently and in parallel reported on the electropolymerization of PEDOT-N 3 , [13] and on synthesis and polymerization of azide-functionalized polypyrrole. [14] In our previous report, we showed that PEDOT-N 3 films can be functionalized with various alkyne-containing molecules, yielding conducting polymer films with new optical (fluorescent) or physical properties (engineered surface free energy).…”
mentioning
confidence: 99%